Ringanui, a new genus of stygobitic amphipod from New Zealand (Amphipoda: Gammaridea: Paraleptamphopidae) - Fenwick, Graham D. (Zootaxa, 2006)
A new genus is established for two new species of paraleptamphopid amphipods. Both species are stygobites inhabiting alluvial aquifers up to at least 18 m beneath the Canterbury Plains in New Zealand. First collected by Charles Chilton in 1882, these two species became confused with Paraleptamphopus subterraneus. The new genus, Ringanui, is a significant step in resolving this confusion. Ringanui differs from Paraleptamphopus on several characters and is most easily recognised by diverse gnathopods, the first of which is enlarged relative to gnathopod 2. The two species are described and illustrated in detail. They differ in size and gnathopod characteristics, but other differences are small. Ringanui koonuiroa is the smaller species and is most easily recognised by the single, very long robust seta defining the palm of gnathopod 1. The second species, R. toonuiiti, is the larger, but its palmar defining spine is relatively short. Both species occur together at the same locations and apparently in the same habitat.